دور الرأسمال النوعي في تحديد الهوية المهنية للمرأة السعودية: سيدات الأعمال بالمنطقة الشرقية نموذجاً - الثقفى، خلود عطية صالح (جامعة الملك عبدالعزيز, 2018)
يدعونا المشهد الحداثي العام بالمملكة العربية السعودية إلى النظر في آليات اشتغال المجتمع السعودي الحديث الذي انخرط في مسارات تنموية ورؤية متطورة استثمرت فيها كل طاقاتها الاقتصادية والبشرية، طاقات شكلت المرأة فيها جزءاً حيوياً بعد أن عززت موقعها وحقوقها التشريعات والقوانين، التي جعلت منها قوى وقع ضخها في شرايين اقتصاد المملكة للمشاركة في شتى المجالات، والنجاح في التموقع داخل المجتمع وخارجه من خلال اعتراف المجتمع الدولي بقدرتها كفاعل مهم في النهوض بالوطن، لذلك جاءت هذه الدراسة كمحاولة للكشف عن واقع طاقات نسائية داخل فضاء مهني عرف في السابق بذكوريته المطلقة، غير أن التغيرات التي عاشتها المملكة منذ عقود أفرز نجاح المرأة في اقتحام هذه المجالات مثل مجال ريادة الأعمال، وعليه فقد اختارت الباحثة أن تبحث في قدرة المرأة السعودية على النجاح في هذا الفضاء المهني من خلال قدرتها على اثبات هويتها المهنية ودور الرأسمال النوعي (الرأسمال الاقتصادي، والاجتماعي، والثقافي، والرمزي، على تحديد هذه الهوية المهنية لسيدات الأعمال بالمنطقة الشرقية كنموذج للدراسة).
The modernist landscape of the Kingdom of Saudi Arabia makes us look at the mechanisms of the modern Saudi society, which has been engaged in development paths and a developed vision to invest all its human and economic energy .Women have formed a vital part of these energies, having strengthened her position and rights through legislations and laws, that have made her an effective force, whose impact has affected the Saudi economy in various fields .The international community has recognized the potential and success of Saudi women in the Kingdom. Therefore, this study came as an attempt to reveal the reality of women's energies within the professional fields that were previously male only. But the changes Saudi Arabia has undergone for decades have made women succeed in many areas, such as entrepreneurship. In this study, we examine the ability of Saudi women to succeed in this professional space through their ability to prove their professional identity, as well as the role of qualitative capital (economic, social, cultural and symbolic) in defining this professional identity of businesswomen in the Eastern Province of Saudi Arabia as a study case.
Keywords: الدور -- الرأسمال النوعي -- الهوية المهنية -- سيدات الأعمال -- المملكة العربية السعودية